Cavitating flow in annular jet pumps. (May 2015) - Xiao, L.; Long, X.
Highlights: Cavitating flow in an annular jet pump is studied by experimental and numerical method. Pump efficiency, pressure ratio and cavitation performance are predicted well compared to experiments. The main characteristics of cavity cloud in annular jet pump under different stages are captured by high speed camera. The dynamic characteristics of cavity cloud are studied through imaging analytical method. The physical mechanism of cavity cloud shedding in diffuser is illustrated. Abstract: Based on the experimental and numerical methods, the pump performance and inner flow details of annular jet pumps under three area ratios (cross sectional area ratio of throat and nozzle) were studied in the present paper. The cavity clouds forming at the shearing layer, recirculation center and throat inlet were captured via high speed video. The realizable k – ε turbulence model combined with mixture cavitation model was well validated by experimental results on the pump performance (pressure ratio and pump efficiency) and the static wall pressure distribution. When the annular jet pump works under the critical working condition, the pressure ratio and the pump efficiency experience a sudden drop. Simultaneously, the flow rate ratio and cavitation number keep constant regardless of the decreasing outlet pressure, since the main flow is filled with cavity clouds. Moreover, the inception and development of cavity cloud induced at the throat inlet were particularly studied in this paper. The cavitation in the throat experiences three stages (incipient, stable and unstable stage) before extending into the diffuser, in which the unstable stage signals the approaching of the critical working condition. The cavity cloud there fluctuates slowly and faintly, while it may suddenly expand over the whole throat and vanish immediately. When the cavity cloud extends into the diffuser with the closure place x / D t < 2.8 ( D t is the diameter of throat length), there is a low frequency cavity cloud surge. However, the surge disappears as the cavity cloud increases to the intermediate part of the diffuser. Additionally, based on imaging analysis method, the frequency characteristic of the cavity shedding in the diffuser was also studied. The shedding of cavity cloud in the diffuser experiences multiple periodicities when L cav = 3.25 D t (cavity length in diffuser), while there are two fundamental frequencies (58 Hz and 6 Hz) for L cav = 1.1 D t with the higher one corresponding to the shedding frequency. In the case of L cav = 3.25 D t, the detached cavity cloud in the diffuser is pushed downstream only by the re-entrant jet. However, the main flow plays an important role on accelerating the detached part downstream in the case of L cav = 1.1 D t .